PERTUMBUHAN DAN KELULUSHIDUPAN BENIH KERAPU TIKUS (Cromileptes altivelis) DENGAN PEMBERIAN HORMON PERTUMBUHAN REKOMBINAN (rGH) MELALUI METODE PERENDAMAN DOSIS BERBEDA - Elvarianna Br G; Usman M Tang; Rusliadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted from 30 Meith to 30th Juni 2016 at Laboratory of Brackish Water Aquaculture Development Centre Situbondo, East Java. This research was aimed to determine the immersion dose of recombinant growth hormone (rGH) to increase growth and viability of seed of river Giant Grouper (Cromileptes altivelis). River Giant Grouper were immerrsed for 30 minutes in water containing 0,9% NaCl, 0,01% Bovine Serum Albumine, and different of dose of rGH ( 0, 6, 12, and 18 mg/l). Each treatment was repeated 3 times. This research concluded that the best dose of recombinant growth hormone was 12 mg/l because it had the highest growth body weight (1,29 g), the higesth growth total length (2,29 cm), the higesth specific growth rate (6,63%, the higest feed efficiency (98, 54%) and the highest survival rate (97,8%) compared the each other dose.Keyword: Cromileptes altivelis, recombinant growth hormone, immersion